Manajemen Perubahan Di Era VUCA - Rani Afkarina; Cindi Septianza; Ahmad Faisol Amir; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Change management in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era has become increasingly important in dealing with business dynamics that change rapidly and unexpectedly. This era is characterized by continuous change, external uncertainty, the complexity of the business environment, and information ambiguity. This study uses the literature study method to explore the concepts and practices of change management that are effective in dealing with the instability and uncertainty of the business environment. Through the research method of literature study, the authors analyze various sources of literature which include change management theories, as well as case studies of the implementation of change management in various organizations. This article highlights the importance of organizational adaptation to rapid and unpredictable environmental change. The study results emphasize continuous adaptation and innovation as the keys to success in the face of constant change. In addition, this article provides insight into how organizations can turn VUCA challenges into opportunities for sustainable growth and development.